Research on the cultivation of cyber security talents under the perspective of double tops based on Jiangsu province - Fu XIAO; Haiping HUANG; Sujun HU; Lijuan SUN (网络与信息安全学报)
Facing the opportunities and challenges in developing the cultivation of cyber security talents in the new security situation, a questionnaire survey on the undergraduate colleges of Jiangsu province, offering network security related majors, is conducted first.Next, multidimensional analysis and comparative study involve eight aspects, such as the distribution scale, the cultivation level, and the curriculum system.Finally, explorations on four aspects, including guarantees of politics, the teaching staff, society, and funds, lead to effective paths on the cultivation of cyber security talents for Jiangsu province under the environment of double tops.